Triangular Approach to Develop a Comprehensive Conceptual Framework to Measure Online Purchasing Intention - Kandambi, G. P. H.; Wijayanayaka, W. M. J. I. (Current Aspects in Business, Economics and Finance Vol. 10, 2023)
E-commerce has the bulk of benefits with many challenges. The identity of the involved parties and verifying the suitability of the goods is still a problem in online purchasing. A New Conceptual framework development was conducted specifically to find a comprehensive model to measure online purchasing intention using four studies. A thematic literature survey was conducted to evaluate theoretical models. Factors identified were grouped and used to build the initial model (M\(α\)) in study one. To pinpoint a key element in the context of e-commerce in research two, technology acceptance models and E-service quality models were thoroughly examined. The second model beta (M\(β\)) was created by integrating the findings of studies one and two and regenerating the components. The third model gamma (M\(σ\)) was created with modest alterations to the second model beta (M\(β\)), according to the Delphi method's results. Further, model gamma (M\(σ\)) was tested utilizing the nominal group technique with industrial experts, and those results confirm model gamma, without modifications, and this was then called model mu (M\(μ\)). Online purchase intention was directly correlated with the constructs of the model, Personal Attributes, Social Influence, Advantage Expectancy, Effort expectancy, Facilitating Conditions, Vendor Quality, Transaction Safety, E-commerce Services, Web Quality, and Trust. The intention to make an online purchase was also indirectly related to vendor quality, transaction safety, e-commerce services, and web quality through trust. The correlations between the model's components and intention to make an online purchase were moderated by age, gender, and expertise.